Clinical aspects of thyroid function during ageing. Issue 9 (September 2018) - Chaker, Layal; Cappola, Anne R; Mooijaart, Simon P; Peeters, Robin P
Summary: Globally, populations are ageing at a rapid rate. The increase in the number of older citizens is accompanied by an increased prevalence of thyroid dysfunction, one of the most common disorders in older people. However, the diagnosis of thyroid dysfunction in older people is hindered by several factors, including the scarcity of thyroid dysfunction symptoms in older people. We describe the physiological changes in thyroid function that occur with increasing age, focusing on literature regarding changes in thyroid function test results in older populations. We also discuss treatment considerations for clinical and subclinical thyroid dysfunction according to international guidelines for older people. Finally, we discuss the relationship between variations in thyroid function and common diseases of old age including cardiovascular disease, osteoporosis, cognitive impairment, and frailty and suggest directions for future research.